ANALISIS KEMAMPUAN KOMUNIKASI DAN SELF EFICACCY SISWA SMA DI BANDUNG BARAT - Rika Nurjanah (Departement of Mathematics Education, 2019)
This paper aims to analyse the notions of student’s mathematical communication skill. In this article no obtained models that can improve communication skills student mathematics but an understanding of mathematical communication, an indicator mathematical abilities, as well as mathematical ability questions that can used to analyse student’s mathematical abilities.